SISI HUMOR DAN CITA RASA KHONG GUAN PADA PUISI-PUISI JOKO PINURBO - Mukodas .; Wildan F. Mubarock (Pedagonal : Jurnal Ilmiah Pendidikan, 2020)
HUMOR AND TASTE OF KHONG GUAN IN JOKO PINURBO’S POEMJoko Pinurbo is one of productive writer. The most interesting part of all works from Jokpin is the humour or jokes he inserted. What makes it interesting there are several poems that he wrote which published in Kompas newspaper on 31st Agustus 2019. There are twelve poems which consists the word Khong Guan in every title: Perjamuan Khong Guan, Hujan Khong Guan, Tidur Khong Guan, Lebaran Khong Guan, Minuman Khong Guan, Sabda Khong Guan, Agama Khong Guan, Keluarga Khong Guan, Mudik Khong Guan, Doa Khong Guan, Bingkisan Khong Guan, dan Hati Khong Guan. Those twelve poems are the subject to this research. The aim of this research is to define how humor was created.  Recent humors are mostly uneducated humor such as insult joke, bullying, and disrespectful. Joko Pinurbo gives alternative in doing humor, through poem. Humor found in the poem is dominated by tragedy humor. Descriptive qualitative method is used in this research. This research found that there are five poems which can be classified as tragedy